Investigation of Antimicrobial Properties of Doscorea pentaphylla from Mid Western Ghats, India - Prakash, G; Hosetti, BB (Scientific World, 2010)
Antibacterial and antifungal activity of crude extracts of medicinally important and traditionally used yam plant Dioscorea pentaphylla from mid Western Ghats was evaluated against 27 bacterial and 5 fungal clinical strains collected of the patients from infectious sources. The clinical strains belonging to their respective species showed concentration dependent susceptibility towards crude petroleum ether extract, chloroform extract and methanol extract at 100ìg/100ìL. All the extracts exhibited predominant antibacterial activity against S. aureus (ATCC-20852), P. aeruginosa (ATCC-29737) and K. pneumoniae (MTCC-618) respectively. and five clinically isolated pathogenic fungi, T. rubrum, M. gypseum, T. tonsurans, M. audouini, and C. albicans with antibacterial drug Ciprofloxacin and antifungal drug Fluconozole (50ìg/100ìL) as the standard drug. Out of three extracts, ethanol extracts possessed better minimum inhibition concentration against all the bacterial strains. All the three extracts showed significant result against all the five fungal pathogen strains. The results are promising and supported the traditional use of D. Pentaphylla for the treatment of bacterial and fungal infections. Keywords : Antifungal; Antibacterial; Crude extracts Dioscorea pentaphylla; MIC and Traditional medicine. DOI: 10.3126/sw.v8i8.3857 Scientific World Vol.8(8) 2010 pp.91-96